The Use of Channel Electrodes in the Investigation of Interfacial Reaction Mechanisms - Unwin, P; Compton, R (1989)
This chapter discusses the use of channel electrodes in the investigation of interfacial reaction mechanisms. The investigation of the kinetics of fast electrode and/or coupled chemical processes demands that mass transport to the electrode is such as to promote competition between, on the one hand, the electrode reaction and, on the other, the transfer of electroactive material away from the electrode before it has chance to react. Whilst this may be achieved in quiescent solution, in principle, by constraining the measurements to short times following a perturbation (of the current or potential) applied to the electrode, problems arise when these times are such that double layer charging competes with the Faradaic process, or components of the system under study are highly adsorptive. An alternative to this strategy, therefore, lies in the addition of convection to the diffusional system. In this way, measurements can be made under steady-state conditions and the rate of mass transport varied by altering the rate of convection.